Hydrothermal Synthesis and DNA Interaction Studies of Copper(II)L Complex - Cao, Yuan-Ying; Xia, Hong; Wang, Lin (Asian Journal of Chemistry, 2011)
The tetraazamacrocyclic complex of copper with the composition Cu(II)L, L = 5,5,7,12,12,14- hexamethyl-1,4,8,11-tetraazamacrocyclic-4,11-diene(ClO4)2, was synthesized by hydrothermal method and characterized by IR spectra and elemental analysis. The interaction of Cu(II)L with calf thymus DNA was studied using viscometry, fluorescence and UV-VIS spectra. Results indicated that the Cu(II)L interacted with DNA is a partial intercalation mode.